Metamorphosis of Traumatic teeth- Aesthetic Rehabilitation with Injection Moulding Technique: A Case Report - Pokhrel, Shrija; Limbu, Senchhema; Dikshit, Parajeeta; Malla, Manisha (Journal of Nepalese Association of Pediatric Dentistry, 2023)
Dental trauma is unpredictable ranging from minor enamel chipping to complete tooth loss, often accompanied by disruptions to the supporting bone and surrounding soft tissues, potentially compromising aesthetics, function, and overall oral health. Individuals experiencing traumatic injuries to the anterior dentition often report compromised aesthetics, impacting their self-esteem and social interactions. This case report describes the use of injection molding technique, for the rehabilitation of incisor crown fractures. The injectable composite resin technique is a versatile treatment for achieving esthetic and functional tooth restoration. This minimally invasive technique can be precisely adjusted to individual needs to replicate natural tooth structures and functions. Here vacuum-pressed vinyl sheet splint has been used as a stent for the injection moulding technique.